Progress in the Research and Development of Anti-COVID-19 Drugs - Huang, Lianzhou; Chen, Yuanqiu; Xiao, Ji; Luo, Weisheng; Li, Feng; Wang, Yuan; Wang, Yiliang; Wang, Yifei (Frontiers in Public Health, 2020)
The outbreaks of COVID-19 due to SARS-CoV-2 has caused serious physical and psychological damage to global human health. COVID-19 spread rapidly around the world in a short time. Confronted with such a highly infectious respiratory disease, the research and development of anti-COVID-19 drugs became an urgent work due to the lack of specific drugs for the treatment of COVID-19. Nevertheless, several existing drugs are available to relieve the clinical symptoms of COVID-19. We reviewed information on selected anti-SARS-CoV-2 candidate therapeutic agents published until June 2, 2020. We also discussed the strategies of the development of anti-COVID-19 drugs in the future. Our review provides a novel insight into the future development of a safer, efficient, and toxic-less anti-COVID-19 drug.